Risks problem of innovations in the production of food - Коломиец, Анна Николаевна; Меленцова, Ольга Владимировна; Базалиева, Алина (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2017)
The article shows that in modern conditions the prospects of development of the sphere of food production are significant at national and international level, attracting investments and intensifying innovation. This requires them to scientific understanding and assessment in terms of risk, which can be generated by ignoring the possible strategic and social impact.Foods production problems on the global and national markets, covering both quantitative and qualitative parameters and are characterized by the increasing relevance. The projected increase in world population by 2050, according to experts of the World Economic Forum in Davos will require double increase food production. Towards solving this problem, which are summarized in the article was devoted to World Expo 2015. The increase in food production during the change of its structure requires significant investment in agriculture and food production, innovative approaches in the development of this sphere. But the assessment of only the economic efficiency of investments at the level of the individual enterprise may generate incorrect orientation for the development of innovation. It is advisable to pay attention to the fact that innovation can lead to both positive and negative consequences for the individual and for society. The article shows the relationship between the growth of sales of low-quality food and an increase in sales of drugs. The authors conclude that the study of the risks of concern innovations in food production, keeping them in business practice, targeting at increasing the production of high-quality foods and the corresponding positioning of Ukrainian goods can be a competitive advantage of Ukrainian producers in the world market.